(untitled) (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
The purpose of this study was to examine whether the activities aimed at developing creative thinking had rendered the social adaptation of adolescents with deviant behaviour smooth and evaluate the changes which had resulted from that engagement. The research data were collected through the use of project checklists, student learning outcomes analysis, interviews with teachers and parents, questionnaires. This study used SPSS and SmartPLS statistical analysis tools to analyze the above data and Textalyser application to process the focus group responses. The study found that the participation of the secondary school students with behaviour deviation in legacy projects make their social adaptation easier, improves their social skills and creative thinking style. This study confirms that there is a positive relationship between socially important creative activities, learning motivation and development of creative thinking styles. It has been found that, despite the considerable amount of research regarding the use of creative activity to develop social adaptation skills in adolescents, the problem of social adaptation of adolescents with behaviour deviation has not been sufficiently explored through engaging them in activities aimed at developing creative thinking. The process of social adaptation of adolescents with behaviour deviation is complex and the creative component is in place there, since it supplies the educational process with irreplaceable pedagogical tools that have the potential to "restart" the student’s physiological and psycho-motivational spheres.